Gluten-Related Disorders: Time to Move from Gut to Brain - Hoggard, Nigel; Sanders, David; Hadjivassiliou, Marios (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The extraintestinal manifestations of coeliac disease (CD) are now well recognised. We have previously edited a special issue for Nutrients covering all aspects of the extraintestinal manifestations in the context of CD. In this issue we wish to concentrate just on the neurological manifestations. The identification of TG6 autoantibodies in patients with neurological manifestations and its use in the diagnosis of such patients seems to be a good opportunity to focus on the neurological aspect of CD. In addition it is now clear that such manifestations can occur even in the absence of enteropathy but in the presence of antigliadin antibodies and/or TG6 antibodies. Given that such antigliadin antibodies can be found in up to 10% of the "healthy" population we anticipate that the neurological manifestations are likely to be very common and thus merit early recognition and treatment.